Formulation Development of Olmesartan Medoxomil Mucoadhesive Buccal Film - Sarojini, Dr. S. (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: Olmesartan medoxomil is an angiotensin II antagonist used in the management of hypertension. Mucoadhesive buccal films offer an attractive route of administration for systemic drug delivery through jugular vein leading to high bioavailability and greater therapeutic efficacy. Materials and Methods: Different formulations were carried out using natural polymer such as almond gum along with synthetic polymers. Formulations of F1 to F8 buccal films were prepared by solvent casting method by employing hydroxypropyl methylcellulose (HPMC) E50LV and almond gum alone, and in combination of HPMC E50LV and Eudragit RL100 and combination of HPMC E50LV and almond gum in different proportions. Results and Discussion: Buccal films were evaluated for their physicochemical characterization such as thickness, weight uniformity, folding endurance, drug content and surface pH, swelling index, percentage moisture loss, and uptake. Conclusion: Among all the formulations, F7 was found to be satisfactory and surface pH of all films was found to be neutral. The in vitro release in optimized formulation F7 was found to be 47.69% in 7 h, and drug release was found to be diffusion following first order as per kinetics (R2 = 0.9937). Stability studies were carried out with selected formulations of F7 and F8.